Characterization and evaluation of joint properties of friction stir welded AA7075/GNPs joints obtained using square and cylindrical threaded tools - Rahul Biradar; Sachinkumar Patil; Nagamadhu M; Priyaranjan Sharma; Filipe Fernandes (Journal of Materials Research and Technology)
This study investigates the joint properties and microstructural features of friction stir-welded (FSWed) AA7075 aluminum alloy composites reinforced with 1 wt % of graphene nanoplatelets (GNPs). It focuses on the influence of square (SQ) and cylindrical threaded (CT) tool pin geometries on material flow, GNPs dispersion, and weld quality. The authors conducted comprehensive evaluations using advanced characterization methods including scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray diffraction (XRD), and Raman spectroscopy. The results reveal formation of precipitates and well bonding between aluminum alloy and GNPs, resulting in better quality of welds. The SQ tool facilitated superior material stirring and uniform dispersion of GNPs, leading to the formation of fine, equiaxed grains in the nugget zone (NZ). Electron back scatter diffraction (EBSD) analysis presents reduction of grain size of base material from 38 μm to 10 μm in the NZ, significantly enhancing mechanical properties. Welds produced using the SQ tool exhibited higher microhardness (150 HV) and tensile strength (630 MPa) compared to those made with the CT tool (141 HV and 478 MPa), resulting in a 75 % improvement in joint efficiency. Fracture analysis revealed ductile failure in the heat-affected zone (HAZ), with fine dimples observed in SEM images. Additionally, the SQ tool weld demonstrated a lower wear rate, reduced from 70 μm to 25 μm, than its counterpart. These findings highlight the importance of tool geometry in producing defect-free, high-performance welds.